MOTORCYCLE DEPENDENCY IN LOW-INCOME PEOPLE : MODELING SPATIAL AND SOCIO-ECONOMIC FACTORS IN URBANIZED AREA OF YOGYAKARTA - Yori Herwangi (Jurusan Teknik Perencanaan Wilayah dan Kota, Fakultas Sains dan Teknologi, Universitas Islam Negeri Alauddin Makassar, 2018)
There are a lot of research on automobile dependency and the factors influencing it that has been done. However, these studies were mostly conducted in developed countries by using a car as the object of research. While the growth in the use of motorcycles in developing countries, especially in Asia has become a phenomenon that is inevitable now, not much is known about the processes and factors that affect motorcycle ownership and dependency in developing countries. Yet according to some studies the majority of motorcyclists are low-income people who should have get more attention from the policy maker. There are allegations that low income people are forced to have a motorcycle because their specific needs cannot be met by existing public transport services. Therefore, by using the urban areas of Yogyakarta as a case study, this study intends to: 1) demonstrate the occurrence of motorcycle dependency in low income people; and 2) model the process of motorcycle dependency in low-income people in terms of spatial and socio-economic factors that influence it. The process of data collection is done through a questionnaire to a sample of 437 low-income households, and interviews with 40 informants. Data from the questionnaire is processed using descriptive and inferential statistics method, while the interview data processed by content analysis method. Based on the analysis it can be concluded that the motorcycle dependency has occurred in low-income people in Yogyakarta urbanized area. The information from the interview was also used for modelling the process of someone becoming a captive users of motorcycle based on their spatial and socioeconomic characteristics. It was found out that there is the different processes that occur for low-income people living in areas with good transport service and the poor one. This assessment of the factors that affect motorcycle dependency on low-income people are expected to give a picture of the areas that should be prioritized in an inclusive policy to increase accessibility of a region, either through improved public transport services or the provision of public facilities that are accessible within a walking distance.